The Interpretasi Keterampilan Proses Sains pada Mata Kuliah Praktikum Mekatronika 2 - Muhammad, Thariq; Habibullah, Habibullah (Jurnal Pendidikan Teknik Elektro, 2024)
This research was conducted to determine the level of Science Process Skills (SPS) of D4 Electrical Industrial Engineering students at Universitas Negeri Padang who programmed the mechatronics 2 laboratory course in the July-December 2023 semester. This type of research falls under quantitative descriptive research. The study is specifically focused on assessing the basic science process skills in the Mechatronics 2 laboratory using data collection techniques such as observation sheets and questionnaires. The research measured the mastery of science process skills by students during the implementation of the Mechatronics 2 laboratory. The results of the study indicate that the science process skills of D4 Electrical Industrial Engineering students in the mechatronics 2 laboratory are classified as insufficient, with a percentage of 60.25%. The highest indicator is classification, falling into the good category with a percentage of 67.57%, while the lowest indicator is communication, categorized as very poor with a percentage of 47.73%. The observation indicator is at 63.01% in the good category, and the indicator of using tools/materials is at 65.50%. Three indicators fall into the insufficient category, namely asking questions (57.82%), planning experiments (57.66%), and conducting experiments (62.48%). Therefore, the science process skills of D4 Electrical Industrial Engineering students at Universitas Negeri Padang in the Mechatronics 2 laboratory need to be further improved.